Effect of MAX Phase Mo2TiAlC2 on the PVDF Ultrafiltration Membrane Properties and Performance - Bandara, H.M.S.N.; Samaranayaka, W.J.M. (Journal of Research Updates in Polymer Science, 2025)
Ultrafiltration membranes are widely used in wastewater filtration due to their efficiency relative to conventional water treatment technologies. To improve the antifouling property of the PVDF membrane, a composite ultrafiltration membrane was fabricated employing the in-situ embedment approach throughout the phase inversion process and utilizing a new 2D material, MAX phase Molybdenum Titanium Aluminium Carbide (Mo2TiAlC2). The membranes were described using Fourier transform infrared spectroscopy (FTIR), Scanning electron microscopy (SEM), and porosity measurements. Rejection tests were applied to study the produced membranes. Adding Mo2TiAlC2 increased the hydrophilicity of the composite membrane compared to the pristine membrane. Porosity and membrane pore size increased with the addition up to 0.6% wt. The most hydrophilic membrane (M3) recorded the highest protein rejection of 84.9%, which was much higher than that of the pristine membrane. These findings highlight the potential of Mo2TiAlC2 as a promising PVDF membrane additive.